2006
DOI: 10.1007/s10661-006-7227-z
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Test for the Determination of Ethylene Sensitivity

Abstract: Ethephon, which releases ethylene within plant tissues after application, was chosen to perform assessments of the relative sensitivity of crops to ethylene and to determine which stages of plant development were most sensitive. The species chosen were: barley, wheat, oats, canola and field pea, all of which are important crops in the province of Alberta, Canada. Plants were treated with ethephon at one of 7 different stages. Plants were assessed for their vegetative and reproductive growth, including height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Low concentration may enhance root elongation, whereas high concentrations se- verely inhibit root elongation, but simultaneously increase root diameter and root hair formation (Marschner 1995). Other authors observed few significant differences between treated and control plants in total vegetative above-ground biomass and root mass in cereals (Archambault et al 2006). The cultivars showed different responses to ethylene treatment in the vegetative stage (cutting) and cut flower stage.…”
Section: Response Of Cuttings and Cut Flowers To Exogenous Ethylene Amentioning
confidence: 86%
See 1 more Smart Citation
“…Low concentration may enhance root elongation, whereas high concentrations se- verely inhibit root elongation, but simultaneously increase root diameter and root hair formation (Marschner 1995). Other authors observed few significant differences between treated and control plants in total vegetative above-ground biomass and root mass in cereals (Archambault et al 2006). The cultivars showed different responses to ethylene treatment in the vegetative stage (cutting) and cut flower stage.…”
Section: Response Of Cuttings and Cut Flowers To Exogenous Ethylene Amentioning
confidence: 86%
“…Ethylene gas has profound effects on a diverse array of plant growth and development processes, including germination, flowering, senescence, abscission, fruit ripening and yield (Archambault et al 2006). A well-known effect of ethylene on plant growth is the so-called 'triple response' of etiolated dicotyledonous seedlings.…”
mentioning
confidence: 99%
“…Thus, foliar application of ethephon at a concentration of 40 mmol L −1 (200 L ha −1 rate) gave an increase in pod numbers for pea (Pisum sativum L.), though final seed yield was unaffected. 90 In the same experimental trial it was found that for ethephon-treated canola (Brassica wileyonlinelibrary.com/jsfa napus L.), barley and wheat plants a decreased reproductive yield occurred only if ethephon was applied during late vegetative and early reproductive stages. Ethephon applied earlier yielded normal (control level) crop yields.…”
Section: Ethylene Ethylene -A Gaseous Hormonementioning
confidence: 99%
“…Although increases in ethylene production often cause retardation of shoot growth, together with reduced reproductive development, this action of ethylene is concentration dependent, with low levels of ethylene production being required for normal (or optimal) plant growth and development . Application of ethylene using the ethylene‐releasing agent, ethephon (or ethrel) can give the desired retardation of shoot growth without affecting crop yield (if applied during early vegetative stages) in cereal species such as barley ( Hordeum vulgare L.) and wheat . Inhibition of shoot growth of cereals without a coincidental inhibitory effect on grain yield is an important commercial use of ethylene in gaining protection from lodging .…”
Section: Ethylenementioning
confidence: 99%
See 1 more Smart Citation